Lime mortars with brick dust and grounded particles for ancient masonry: development and evaluation - Matias, Gina (2014)
HMC08 - 1st Historical Mortars Conference: Characterization, Diagnosis, Conservation, Repair and Compatibilit, LNEC, Lisbon, 24-26 September 2008